Estudo cromossômico em espécies de Rineloricaria (ACTINOPTERYGII: SILURIFORMES: LORICARIIDAE): diversidade cariotípica e DNAs repetitivos - Primo, Cleberson Cezario (2015)
The Loricariidae family (Actinopterygii: Siluriformes) is morphologically diverse, has a number close to 900 valid species, distributed in seven subfamilies (Lithogeneinae, Delturinae, Neoplecostominae, Hypoptopomatinae, Loricariinae, Ancistrinae and Hypostominae). However, cytogenetic studies in species of the family show evolutionary trends of karyotype diversification well defined for each of the subfamilies and the diploid number (2n) of 54 chromosomes is considered basal. Among the representatives of the subfamily Loricariinae, the variation of 2n is 36 to 74 chromosomes. Given these data, the Robertsonian rearrangements are the main mechanisms to explain the chromosome number variation in the subfamily. Rineloricaria is the most specious genus of Loricariinae, porting species with 2n = 36 to 2n = 70 chromosomes. However, little is known about what types of repetitive DNAs originate fission and fusion chromosome events. In this study, species of Rineloricaria from different rivers of the Paraná drainage were studied: Rineloricaria latirostris (Laranjinha river, Cinzas basin and Barra Grande river, Ivaí basin); Rineloricaria pentamaculata (Barra Grande and Juruba rivers, Tibagi basin); and, Rineloricaria stellata and Rineloricaria capitonia (Upper Uruguai river). The aim of this study was to characterize the karyotypes of populations/species of Rineloricaria and to check what types of repetitive DNAs may be related to Robertsonian events in the genus. In R. latirostris was detected 2n = 46 chromosomes for both populations, as well as for a triploid specimen from Laranjinha river. Rineloricaria pentamaculata had 2n = 56 chromosomes to populations from Barra Grande and Juruba rivers and a karyomorph in Barra Grande river with 2n = 54 chromosomes. Rineloricaria stellata had 2n = 54 chromosomes, while R. capitonia presented 2n = 64 chromosomes, both from the Uruguai river. The results using the chromosomal markers of 18S rDNA, 5S rDNA and TTAGGGn telomeric probe showed that these repetitive DNAs participated in end to end fusions of the st/a chromosomes in the karyotype diversification of R. latirostris. Vestiges of interstitial telomeric sites (ITS) were also detected in R. pentamaculata, karyomorph of 54 chromosomes from the Barra Grande river, suggesting chromosomal fusion to the diversification of this karyotype. The wide range of 2n between R. stellata and R. capitonia is compatible to the reproductive isolation of syntopic species and the diversification of R. capitonia can be explained by centric fusions. In addition to Robertsonian rearrangements, the pericentric inversions also assisted in the diversification of karyotypic formulas among the species/populations. In situ localization analysis using the transposable element Tc1-Mariner Like probe showed no evidence of the participation of transposon in chromosomal rearrangements and dispersion of multiple sites of 5S rDNA in Rineloricaria. Furthermore, analyzes of the Tc1-Mariner Like sequences showed intense molecular degeneration, especially in transposase domains. These results indicate the absence of activity of these sequences, which must be inert or serve to other genomic functions in the genus. Thus, this study discusses the telomeric instability, repetitive DNAs and the participation of rDNA gene families in karyotype diversification events in Rineloricaria.